Cardiovascular-renal protective effect and molecular mechanism of finerenone in type 2 diabetic mellitus - Lv, Ruolin; Xu, Lili; Che, Lin; Liu, Song; Wang, Yangang; Dong, Bingzi (Frontiers in Endocrinology, 2023)
Chronic kidney diseases (CKD) and cardiovascular diseases (CVD) are the main complications in type 2 diabetic mellitus (T2DM), increasing the cardiovascular and all-cause mortality risk. Current therapeutic strategies that delay the progression of CKD and the development of CVD include angiotensin-converting enzyme inhibitors (ACEI), angiotension II receptor blockers (ARB), sodium-glucose co-transporter 2 inhibitors (SGLT-2i) and GLP-1 receptor agonists (GLP-1RA). In the progression of CKD and CVD, mineralocorticoid receptor (MR) overactivation leads to inflammation and fibrosis in the heart, kidney and vascular system, making mineralocorticoid receptor antagonists (MRAs) as a promising therapeutic option in CKD and CVD. Finerenone is the third generation highly selective non-steroidal MRAs. It significantly reduces the risk of cardiovascular and renal complications, improves the cardiovascular-renal endpoints in T2DM patients combined with CKD and chronic heart failure (CHF). It is safer and more effective than first- and second-generation MRAs due to its higher selectivity and specificity, resulting in a lower incidence of adverse effects including hyperkalemia, renal insufficiency and androgen-like effects. Finerenone shows potent effect on improving the outcomes of CHF, refractory hypertension, and diabetic nephropathy. Recently studies have shown that finerenone may have potential therapeutic effect on diabetic retinopathy, primary aldosteronism, and atrial fibrillation. In this review, we discuss the safety and efficacy of clinical application of finerenone and its molecular mechanism. We hope to provide new insights for the clinical application and therapeutic prospect.